La Lucha: framing the struggle for survival, double consciousness and the economy of identity for undocumented Latina/os. - Scott, Jennifer (Journal of Ethnic & Migration Studies, 2023)
Undocumented Latina/os often describe their lives as 'la lucha', the struggle. To make ends meet 'hay que batallar', one must battle, work hard to 'salir adelante', get ahead. La lucha is interpretable as a frame that demarcates how undocumented Latina/os employ the performance of economic tasks to establish both individual and collective identity in the United States. Although claiming positive elements of racialised stereotypes as coping mechanisms and racialised illegality have been separately theorised, they have not been brought together in a theory of self. I use W.E.B. Du Bois's concept of 'double-consciousness', the sensation of "looking at one's self through the eyes of others" that articulates Black Americans' experience of racism to illuminate how the lucha frame resolves a conflict resonant in undocumented Latina/o identity. In the words of undocumented Latina/os from interviews in a Texas city, I illustrate how double consciousness reveals the simultaneity of uplift and collective struggle. It illuminates through la lucha the linkage of the context of the 'struggle' to internalization of the hard worker archetype, engaging these contradictory perspectives in a single identity. The existential elements of la lucha highlight need for policy addressing the liminality of undocumented life and instability of precarious work.